Conversion of Biomass to Adsorbent: A Review - Ngulde, A. B.; Silas, K.; Mohammed, H. D.; Yaumi, A. L.; Taura, U. H.; Mari, H. H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Tons of biomass are produced every year including organic agricultural and forestry by-products but they are of limited value. Mostly, in the developing countries, the biomasses are considered as waste and are being burnt or thrown to liter the environment as part of teaming solid waste. Presently, there are no sustainable long-term management strategies to use biomass. The utilization of biomass to produce activated carbon is a good approach that is industrially useful and environmentally benign materials. The adsorption technique is using adsorbents in the removal of heavy metals from water therefore, biomass can be converted to the adsorbent and utilized as a waste-to-wealth commodity in water purification. In this review, the suitable process for conversion of biomass to cheap and simple means of obtaining activation carbon as adsorbent is presented. The potential uses of biomass and the conversion stages including carbonization, pyrolysis, gasification, and activation were discussed. This work depicts that the issue of solid waste utilization to solve existing issues with locally available and cheap materials is beneficial to man and the environment.